A Critical Evaluation of Current Methods for Exercise Prescription in Women and Men - Iannetta, Danilo; Inglis, Erin Calaine; Mattu, Anmol T; Fontana, Federico Y; Pogliaghi, Silvia; Keir, Daniel A; Murias, Juan M (Medicine and science in sports and exercise, 2020)
Common methods to prescribe exercise intensity are based on fixed percentages of maximum rate of oxygen uptake (V˙O2max), peak work rate (WRpeak), maximal HR (HRmax). However, it is unknown how these methods compare to the current models to partition the exercise intensity spectrum. Thus, the aim of this study was to compare contemporary gold-standard approaches for exercise prescription based on fixed percentages of maximum values to the well-established, but underutilized, "domain" schema of exercise intensity. One hundred individuals participated in the study (women, 46; men, 54). A cardiopulmonary ramp-incremental test was performed to assess V˙O2max, WRpeak, HRmax, and the lactate threshold (LT), and submaximal constant-work rate trials of 30-min duration to determine the maximal lactate steady-state (MLSS). The LT and MLSS were used to partition the intensity spectrum for each individual in three domains of intensity: moderate, heavy, and severe. V˙O2max in women and men was 3.06 ± 0.41 L·min and 4.10 ± 0.56 L·min, respectively. Lactate threshold and MLSS occurred at a greater %V˙O2max and %HRmax in women compared with men (P < 0.05). The large ranges in both sexes at which LT and MLSS occurred on the basis of %V˙O2max (LT, 45%-74%; MLSS, 69%-96%), %WRpeak (LT, 23%-57%; MLSS, 44%-71%), and %HRmax (LT, 60%-90%; MLSS, 75%-97%) elicited large variability in the number of individuals distributed in each domain at the fixed-percentages examined. Contemporary gold-standard methods for exercise prescription based on fixed-percentages of maximum values conform poorly to exercise intensity domains and thus do not adequately control the metabolic stimulus.